2020
DOI: 10.2196/13980
|View full text |Cite|
|
Sign up to set email alerts
|

A Facilitated Web-Based Self-Management Tool for People With Type 1 Diabetes Using an Insulin Pump: Intervention Development Using the Behavior Change Wheel and Theoretical Domains Framework

Abstract: Background Type 1 diabetes (T1D) requires intensive self-management (SM). An insulin pump is designed to better support personal T1D management, but at the same time, it exacerbates the complexity and requirements of SM. Research shows that people with diabetes are likely to benefit from navigating and connecting to local means of social support and resources through web-based interventions that offer flexible, innovative, and accessible SM. However, questions remain as to which behavior change mec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…Zuidema et al [ 19 ] did not find any positive effects associated with a web-based tool to support self-management. This was surprising as the interventions were similar in both content and theory to other online self-management interventions which show positive effects in other chronic conditions [ 44 46 ]. Zuidema et al [ 19 ] concluded that this could be due to the outcome measures chosen or perhaps the need to add a tailoring aspect to their intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Zuidema et al [ 19 ] did not find any positive effects associated with a web-based tool to support self-management. This was surprising as the interventions were similar in both content and theory to other online self-management interventions which show positive effects in other chronic conditions [ 44 46 ]. Zuidema et al [ 19 ] concluded that this could be due to the outcome measures chosen or perhaps the need to add a tailoring aspect to their intervention.…”
Section: Discussionmentioning
confidence: 99%
“…52 The BCW 54 55 is a 'theory and evidence based' intervention development approach 58 that provides guidance on considering and identifying the function of interventions (eg, education, persuasion, enablement) and policy categories that may support the delivery of these functions (eg, guidelines, service provision, environmental planning) and how these both link to MoAs and/or BCTs. The TDF and related resources have been used to inform the development and evaluation of health-focused behavioural interventions, [59][60][61] including informing the data collection and/or analysis of qualitative studies forming an early stage in the process of intervention development. [62][63][64][65] Data collection: interview content and procedures Participants will take part in one semistructured qualitative interview lasting around 45 min, though duration is likely to be variable depending on how much a participant wishes to say and their preferred interview pace.…”
Section: Theoretical Framework Informing Data Collection and Analysismentioning
confidence: 99%
“…For example, the "Theoretical Domains Framework" synthesizes theories of behavior change into 14 "domains" [19,20] that reflect major influences on enacting a behavior (TDF; see S1 File for domains and definitions) [21]. Barriers and enablers to behavior identified by the TDF can be combined with other frameworks (Behaviour Change Wheel (BCW); Expert Recommendations for Implementing Change (ERIC)) [21][22][23] to guide development of strategies to help adopt behaviors of interest [21,[24][25][26][27][28][29]. In the present study, we drew upon this approach to interview preclinical scientists and systematically examine the barriers and enablers to using preclinical guidelines and identify strategies that might improve their uptake.…”
Section: Introductionmentioning
confidence: 99%